Reactive melt infiltrated Cf/SiC composites with robust matrix derived from novel engineered pyrolytic carbon structure. Issue 7 (May 2017) - Zhong, Qiang; Zhang, Xiangyu; Dong, Shaoming; Yang, Jinshan; Hu, Jianbao; Gao, Le; He, Ping; Zhou, Haijun; Wang, Zhen; Ding, Yusheng
Abstract: Needle-punched Cf /SiC composites were fabricated by a novel pore tuned reactive melt infiltration (RMI) process. The novel hierarchically porous carbon structure in the fiber preform with the porosity well open to liquid silicon was engineered by impregnation of phenolic resin with addition of a pore former. Neither residual bulk carbon nor residual bulk silicon is detected in the matrix of the Cf /SiC composites prepared by the pore tuned RMI, indicating that a robust matrix with homogenous SiC can be formed. The composite prepared by the pore tuned RMI exhibits a tensile strength of 159±5 MPa, which is 46% higher than that without addition of pore former.